The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1523/jneurosci.5215-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stress Modulates Motor Patterning via AMP-Activated Protein Kinase

Abstract: Neural circuits are especially vulnerable to metabolic stress. The locust (Locusta migratoria) responds to anoxia by entering a coma during which neural and muscular systems shut down. During anoxic coma, arrest of the ventilatory central pattern generator is tightly correlated with an abrupt spreading depression (SD)-like increase in extracellular potassium concentration within the metathoracic neuropile. We examined the role of the AMP-activated protein kinase (AMPK), an evolutionarily conserved sensor of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…This response is consistent with previous studies on insects (Wegener, 1993;Weyel and Wegener, 1996;Campbell et al, 2018) and the stability of a low but non-zero ATP tissue concentration could indicate a regulated ATP homeostasis (Boutilier, 2001;Campbell et al, 2018). Entering coma when exposed to environmental stressors such as anoxia can in some respects be considered an adaptive mechanism as coma decreases energy demand (Rodgers-Garlick et al, 2011). Energy production of the hypometabolic L. migratoria is seemingly supported by anaerobic metabolism, as indicated by the hemolymph pH decrease of ∼0.8 units within the first 2 h of anoxia (Fig.…”
Section: Anoxia Causes Disruption Of Homeostasissupporting
confidence: 91%
“…This response is consistent with previous studies on insects (Wegener, 1993;Weyel and Wegener, 1996;Campbell et al, 2018) and the stability of a low but non-zero ATP tissue concentration could indicate a regulated ATP homeostasis (Boutilier, 2001;Campbell et al, 2018). Entering coma when exposed to environmental stressors such as anoxia can in some respects be considered an adaptive mechanism as coma decreases energy demand (Rodgers-Garlick et al, 2011). Energy production of the hypometabolic L. migratoria is seemingly supported by anaerobic metabolism, as indicated by the hemolymph pH decrease of ∼0.8 units within the first 2 h of anoxia (Fig.…”
Section: Anoxia Causes Disruption Of Homeostasissupporting
confidence: 91%
“…In mammals [25] and locusts [21], [22], [26], [27] mimicking the effect of energetic compromise with the Na + /K + -ATPase inhibitor ouabain generates spontaneous SD similar to PID. To determine if a similar phenomenon could occur in the fly brain we exposed flies to volatilized ouabain (10 µl of 100 mM; see e.g [28]…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that AMPK inhibition using compound C, a selective and ATP-competitive inhibitor of AMPK, reversed the effect of AICAR, an AMPK activator. 27,28) Our results showed that the phosphorylation of AMPK induced by AglRhz was inhibited by compound C (Fig. 2C), suggesting that AglRhz may exert its antitumor effect in HT-29 cells via AMPK activation.…”
Section: Discussionmentioning
confidence: 73%